Surgical treatment for a rare case of ectopic tooth in the lateral wall of the nasal cavity - De Bortoli, Manoela Moura; Arruda, José Alcides Almeida de; Vasconcellos, Ricardo José Holanda; Oliveira e Silva, Emanuel Dias; Tormes, Ana Karina de Medeiros; Moreno, Amália; Sobral, Ana Paula Veras (ARCHIVES OF HEALTH INVESTIGATION, 2020)
Among the ways to approach cases of ectopic teeth, the surgical approach is a valid option and should be considered, since it is considered simple and it permits direct visualization and a rapid recovery. The aim of this article is to report a rare case of ectopic tooth in the lateral wall of the nasal cavity caused by trauma in the maxillofacial region in childhood, and to describe its clinical and imaging characteristics as well as ways of treatment and surgical aspects. A 25-year-old woman was seen at the clinic of Maxillofacial Surgery and Traumatology due to the presence of a foreign body in the nose. A treatment plan was elaborated based on physical and radiographic examination. The tooth was removed by a surgical approach and the patient underwent esthetic rehabilitation. Surgical treatment of ectopic teeth provides a good and satisfactory postoperative result, is simple and mostly without complications. Ectopic teeth are rare, and the professional should be able to perform the diagnosis, indication and planning of treatment, as well as its execution. Surgical treatment is an option that produced an effective result in the present case. Descriptors: Mouth; Tooth, Impacted; Ambulatory Surgical Procedures. References Verma RK, Bakshi J, Panda NK. Ectopic intranasal tooth: an unusual cause of epistaxis in a child. Ear Nose Throat J. 2012;91(6):242-44. Gupta YK, Shah N. Intranasal tooth as a complication of cleft lip and alveolus in a four years old child: case report and literature review. Int J Paediatr Dent. 2001;11(3):221-24. Thor AL. Delayed removal of a fully intruded primary incisor through the nasal cavity: a case report. Dental Traumatol. 2002;18(4):227-30. Koçak HE, Özdamar K, Bilgi B, Aipayam H. Case report a rare cause of intranasal mass: bilateral ectopic nasal teeth. Iran J Otorhinolaryngol. 2017;29(94):287-89. Van Essen TA, Van Rijswijk JB. Intranasal toothache case report. J Laryngol Otol. 2013;127(3):321-22. Kim DH, Kim JM, Chae SW, Hwang SJ, Lee SH, Lee HM. Endoscopic removal of an intranasal ectopic tooth. Int J Pediatr Otorhinolaryngol. 2003;67(1):79-81. Ray B, Singh LK, Das CJ, Roy TS. Ectopic supernumerary tooth on the inferior nasal concha. Clin Anat. 2006;19(1):68-74. Zalagh M, Akhaddar A, Benariba F. Chronic rhinorrhea revealing an actinomycotic rhinolithiasis with ectopic tooth. Int J Oral Maxillofac Surg. 2012;41(3):297-99. Moreano EH, Zich DK, Goree JC, Graham, SM. Nasal tooth. Am J Otolaryngol. 1998;19(2):124-26. Sammatino G, Trosino O, Perillo L, Cioff A, Marenzi G, Mortellaro C. Alternative transoral approach for intranasal tooth extraction. J Craniofac Surg. 2011;22(5):1944-46. Lee FP. Endoscopic extraction of an intranasal tooth: a review of 13 cases. Laryngoscope. 2001;111(6):1027-31.